SUBACUTE TOXICITY TEST OF BEACH CABBAGE [Scaevola taccada (Gaertn.) Roxb.] LEAF EXTRACT ON HISTOPATHOLOGICAL CHANGES IN THE LIVER AND KIDNEYS OF WHITE RATS - Widati, Aritzah Dwi; Adri, Tenri Ayu; Kabo, Peter; Djabir, Yulia Yusrini (Universitas Syiah Kuala, 2022)
The purpose of this study was to evaluate the toxic effects of beach cabbage leaves [Scaevola taccada (Gaertn.) Roxb.]by observing the histopathological changes in the livers and kidneys of male white rats. This study used 20 white rats which were divided into 4 groups: 1 control group and 3 groups receiving treatments in the form of Scaevola taccada leaf ethanolic extract (STLEE) in graded doses (200 mg/kg BW, 400 mg/kg BW, and 600 mg/kg BW). Toxicity test was performed by administering STLEE for 14 days. The results of daily observations showed that the experimental animals experienced diarrhea. Meanwhile, histopathological observations showed the occurrences of hydropic degeneration, fat degeneration, necrotic liver cells, and dilatation of Bowman's capsule in the animals kidney cells. It was concluded that STLEE at a dose of 200 mg/kg BW is safe to use, but is toxic at a dose of 600 mg/kg BW, both to the livers and kidneys.